Kebijakan Pemerintah Terhadap Pendidikan Di Indonesia Menuju Perguruan Tinggi Unggul - Yayuk Zulaikah; Mujamil Qomar; Abd. Aziz (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The purpose of writing this article is to find out the government's policy towards education in Indonesia towards superior universities. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that achieving accreditation for PTKIN is now an absolute necessity. Because institutional accreditation is a set of assessments that directly evaluates the management and quality of each higher education institution. Since 2020, accreditation assessment for new universities and study programs has been implemented based on 9 criteria, so that in the future the accreditation process for these two study programs will use an assessment system based on 9 criteria. Realizing PTKIN to be able to achieve an A (excellent) accreditation score can be done through a technical management approach to superior PTKIN institutional accreditation. This technical management is the basis for preparing forms and complete documents and the accreditation visitation process. Technical management covers a fairly broad scope. So that ideally technical management is understood comprehensively by higher education administrators. So that institutional accreditation can reach an A (excellent) grade.